2002
DOI: 10.2174/1381612023395349
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for New Antimicrobial Proteins and Peptides: Lysozyme and Aprotinin as Model Molecules

Abstract: The increasing development of bacterial resistance to traditional antibiotics has reached alarming levels, thus necessitating the strong need to develop new antimicrobial agents. These new antimicrobials should possess both novel modes of action as well as different cellular targets compared with the existing antibiotics. Lysozyme, muramidase, and aprotinin, a protease inhibitor, both exhibit antimicrobial activities against different microorganisms, were chosen as model proteins to develop more potent bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 0 publications
1
73
0
Order By: Relevance
“…Alternatively, lysozyme at later stages of development may undergo enzymatic hydrolysis by certain proteases that produce fragments of the enzyme with enhanced activity. It has been shown that the hydrolysis of lysozyme by different proteolytic enzymes, such as clostripain, pepsin and trypsin, caused the exposure of the antibacterial peptides of the enzyme, and as a result increased its antibacterial activity (Pellegrini et al 1997;Ibrahim et al 2001Ibrahim et al , 2002Ibrahim et al , 2005Mine et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, lysozyme at later stages of development may undergo enzymatic hydrolysis by certain proteases that produce fragments of the enzyme with enhanced activity. It has been shown that the hydrolysis of lysozyme by different proteolytic enzymes, such as clostripain, pepsin and trypsin, caused the exposure of the antibacterial peptides of the enzyme, and as a result increased its antibacterial activity (Pellegrini et al 1997;Ibrahim et al 2001Ibrahim et al , 2002Ibrahim et al , 2005Mine et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Egg white lysozyme consists of 129 amino acid residues with a molecular weight of 14.4 kDa. Because of its basic character, lysozyme binds to ovomucin, transferrin or ovalbumin in egg white [58]. In nature, lysozyme is found mainly as a monomer but it has been reported to also exist as a reversible dimer, which can be evoked by pH, concentration and/or temperature-dependent phase transition of the molecule.…”
Section: Lysozymementioning
confidence: 99%
“…Enzymatic hydrolysis of lysozyme is a novel technology that uses proteolytic enzymes for hydrolyzing native lysozyme to produce potent antimicrobial peptides that hidden within its folds. Lysozyme was digested by different proteolytic enzymes, such as clostripain [58,60], pepsin, and trypsin [97,98,99]. All these researchers proved that the resulting peptides lost the enzymatic activities of lysozyme, but exhibited strong bactericidal activities against both Gram-negative (E.coli, Salmonella, Pseudomonas, and Aeromonas) and Gram-positive bacteria (Listeria monocytogenes, Staph aureus, Bacillus spp., and Leuconostics spp.)…”
Section: Lysozyme Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative bacteria, however, are not directly damaged by lysozyme as their outer membrane is significantly coated with lipopolysaccharide (LPS) moieties. Instead, the outer membranes of Gram-negative bacteria must first be disrupted by cationic antimicrobial peptides that expose the inner peptidoglycan layer of bacteria to lysozyme (Banks et al, 1986;Hancock and Scott, 2000;Ibrahim et al, 2002).…”
Section: Introductionmentioning
confidence: 99%